Minutes of 12th technical and progress monitoring (TPM) meeting of BRACU new campus (session ll) - Brac University (Brac University, 2023)
Minutes of the 12th Technical and Progress Monitoring (TPM) meeting (session Il) of BRACU new campus, held on 9th March, 2019.